Green Synthesis, Characterization and Antimicrobial Activity of Silver Nanoparticles Using Locally Growing Allium Sativum Extract - Twana Mohammed M.Shafea; Kamal M. Mahmoud (Zanco Journal of Pure and Applied Sciences, 2021)
In the present paper, a green synthesis of silver nanoparticles (AgNPs) have been prepared using Allium sativum (garlic) extract(GE) (growing in Kurdistan-Iraq) at 60 – 65 Cº, The synthesized silver nanoparticles were characterized by UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), Scanning Electron microscopy (SEM), X-ray diffraction (XRD) and Energy-Dispersive X-ray spectroscopy(EDX). The UV-Visible spectroscopy of synthesized AgNPs showed absorption maxima at 433 nm. The XRD examination implied that AgNPs support the equalizer with an average crystallite size of 15 nm. Antimicrobial activity of prepared nanoparticles (two different concentrations) and extracted garlic was done. It has an effect on the growth of three microorganisms (Micrococcus sp. (gram positive bacteria); Pseudomonas aeruginosa (gram negative bacteria) and Candida albicans (fungus)). The most important interests of this preparation are safe, fast and it has activity against bacterias and fungus.